Alcohol consumption and utilization of HIV prevention services among men who have casual sex with women in China. Issue 4 (3rd April 2023) - Jiao, Kedi; Wei, Ran; Lin, Yuxi; Li, Chuanxi; Wang, Lin; Ma, Wei
ABSTRACT: Men who have casual sex with women (MCSW) have played an important role in HIV new infections in China. Research studies have shown that heavy alcohol consumption can increase the risk of HIV infection. The cross-sectional study was conducted in two cities in China from December 2018 to May 2019 to examine the association between alcohol consumption and utilization of HIV prevention services among MCSW. Convenience sampling was used to recruit participants and 400 MCSW were recruited in this study. There were 238 (59.6%), 213 (53.4%) and 129 (32.4%) participants having utilized HIV prevention services, condom promotion and distribution or HIV counseling and testing (CPD/HCT) services, and peer education services in the past 12 months, respectively. MCSW who were identified as heavy drinkers were less likely to utilize HIV prevention services and CPD/HCT services compared with non-drinkers. For youngsters, those who are in the local household and those who are married/cohabitating, heavy drinkers was less likely to utilize HIV prevention services. This study highlights the significance of intensive education on heavy drinkers of MCSW, particularly for high-risk subgroups. Targeting resources for integrated HIV prevention efforts with alcohol-using MCSW should be considered by public health policymakers.